Adaptation to climate change in small coastal cities: The influence of development status on adaptation response. (1st October 2021) - O'Donoghue, Sean; Lehmann, Martin; Major, David; Major-Ex, Graham; Sutherland, Catherine; Motau, Andries; Haddaden, Nancy; Kibria, Abu SMG.; Costanza, Robert; Groves, Colin; Behie, Alison; Johnson, Katie
Abstract: In contrast to coastal towns and small urban settlements, small coastal cities (population of between 50, 000 and 100, 000) may exhibit comparable knowledge and planning infrastructure as larger cities or be similarly connected to research institutions. However, at a global level, there is little statistical data about small cities, and their numbers and locations are thus so far unknown. In this paper, five cases of small coastal cities, two of which are located in the USA - Miami Beach and Milford - and three, in Australia (Mandurah), Bangladesh (Sundarbans), and South Africa (Knysna) respectively, are presented and discussed in view of adaptation to climate change. All cases reported vulnerability to sea level rise, with impacts compounded by increasing storminess (and even hurricanes of increasing intensity), tides, inland flooding and loss of natural habitat. Changes in precipitation resulted in both reduced river flow, leading to sediment deficits and coastal erosion (from the sea) or increased river flow with similar damage (from the land). Adaptation response was most clearly delineated along lines of development status with wealthier, more highly developed cities pursuing more technologically advanced solutions, whilst the two cities of the Global South focused more on governance and capacity building solutions. Also, it was clear from the Knysna case that if a city or municipality lacks the capacity to effectively respond with adaptation measures, local private wealth may dominate and result in haphazard adaptation responses to the detriment of regional adaptation planning efforts. While this paper provides a first step in establishing a richer understanding, it is clear that more case studies across global regions and economic categories are required to deepen our understanding of climate change adaptation planning in small cities. Highlights: All case studies are experiencing impacts related to climate change, either through sea level rise or changes in rainfall. Climate change impacts are exacerbated by human-related co-impacts, like inappropriate development or land use changes. There is a clear difference in response, particularly in technology embraced, between cities from the Global North and South.